Workaholism in organizations, Volume 11, Issue 5 : New research directions. - Snir, Raphael (Emerald Group Pub., 2006)
An international collection of papers on the topic. The editors and authors explain the need for more research on the topic. An interesting and useful addition to a special issue is the Epilogue which both comments on the special issue itself and clearly explains the research implications and future directions.